Using Regulatory technology (Regtech) to increase compliance - Piiparinen, Outi (My University, 2021)
The revolution of technology all around the world has modified and revolutionized banking services and data protection. This has pushed Financial institutions to become more creative ad for the first time put compliance to spotlight. There has been new proposals and legal changes to the field and regulators are more interested on the subject than ever before. This master’s thesis has the intention of providing a comprehensive analysis of the existing conditions financial institutions are under and what kind of factors should they be taking into consideration to get effective compliance to maintain and reach affordable, secure and competitive gap in the market. I will also focus on what kind of challenges are they facing now and possibly in the future. Besides the theoretical and historical background, this thesis pays considerable attention to the practical side of the matter. It will present diverse implementation examples of how financial institutions have been moving forward and learned to use the benefits provided by Artificial intelligence. It will also include inside information, opinionated discussion and a predictive analysis.